Intelligent and Efficient Electrical Systems Selected Proceedings of ICIEES'17 - Bhuvaneswari, M.C.; Saxena, Jayashree; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book presents selected papers from International Conference on Intelligent and Efficient Electrical Systems (ICIEES'17). The volume brings together content from both industry and academia. The book focuses on energy efficiency in electrical systems and covers en trende topics such as control of renewable energy systems. The collaborative industry-academia perspective of the conference ensures that equal emphasis is laid on novel topics and practical applications. The contents of this volume will prove useful to researchers and practicing engineers alike.
Multi-objective optimization of standalone renewable energy hybrid system -- Wind Farm Power Prediction Based on Wind Speed and Power Curve Models -- Integration of Wind Power Generators for the Enhancement of Profit by Optimal Allocation of SVC -- Fractional Order Controller Design and Analysis for SEPIC Converter -- Advanced Energy Management of a Micro-Grid using Arduino and Multi Agent System -- Optimal Single and Multiple DG Installation in Radial Distribution Network Using SLPSO Algorithm -- Dynamic Modeling and Control of Utility Interactive Microgrid Using Fuzzy Logic Controller -- Torque Ripple Minimization of a FOC fed PMSM with MRAS using Popov's Hyper stability criterion -- Effectual particle swarm optimization algorithm for the solution of non-convex economic load dispatch problem -- Application of Cuckoo Search Algorithm in Deregulated Economic Load Dispatch -- Investigation on the properties of natural esters blended with mineral oil and pyrolysis oil as liquid insulation for high voltage transformers -- Implementation of Mesh Network Using Bluetooth Low Energy Devices -- Online Static Security Assessment Module using Radial Basis Neural Network Trained with Particle Swarm Optimization -- Performance Analysis of Wavelets function using Denoising for Clinical Database -- Influence of switching frequency of  PWM waveform on breakdown in Twisted Pairs -- Diagnosis of Cardiovascular Diseases (CVD) using Medical Images.
Keywords: Electric power production; Multibody systems; Vibration; Mechanics, Applied; Electrical Power Engineering; Mechanical Power Engineering; Multibody Systems and Mechanical Vibrations